Differentiated Approach to Improving the Physical Qualities of Students With Disabilities - Gofurov Sherali Hoshimovich; Gofurov Bakhodir Hoshimovich; Kholmurzaev Shakhboz Ibragim o’g’li; Kholmirzayev Sabina Ilhom qizi (Genius Journals, 2022)
The author in this article scientifically substantiated a differentiated approach to improving the physical qualities of students with disabilities using a special program. The program developed by the author included five nosology tests for girls with disabilities in series.
Keywords: differentiated approach; physical qualities; tests; program